Factors that influence the intention of agriculture programmes students as entrepreneurs - Azman, Nur Anis Athirah (2018)
In view of Malaysia government’s vision to transform its economy from knowledge-based to innovation in its aspiration to be the high-income country by 2020, the students from higher education institutions should be exposed with the entrepreneurial skills. The entrepreneurship has the great potential to develop economic growth. The various policies and programs have been established to encourage more graduates engaged in entrepreneur as a career. The Malaysian government also has given special attention to entrepreneurship as an alternative to facilitate and improve the industrial structure in order to create industries for the future generations. The unemployment problems among graduates become a big issue and create problem to the government. The entrepreneurship is considered as one of the best alternatives to overcome the graduate unemployment problems in Malaysia. Thus, the purpose of this study was to investigate the factors that influenced the intention of students as entrepreneurs. The qualitative method used in this study involved 350 respondents who are agriculture programmes students from Faculty of Agriculture, Universiti Putra Malaysia. The data was analyzed by using three statistical methods such as descriptive analysis, chi-square analysis and factor analysis. The chi-square analysis showed the association between socio-demographic backgrounds and intention to be an entrepreneur. There were four factors that influenced the intention of agriculture programmes students as entrepreneur namely attitudes, personal attributes, family influence and education.